Research on land-cover classification methodologies for optical satellite images - Mẫn, Đức Chức (Trường Đại học Công nghệ, 2018)
CHAPTER 1. INTRODUCTION. CHAPTER 2. THEORETICAL BACKGROUND. CHAPTER 3. PROPOSED LAND COVERCLASSIFICATION METHOD. CHAPTER 4. EXPERIMENTS ANDRESULTS. CHAPTER 5. CONCLUSION